SUSTAINABLE SMART SOCIAL ENTREPRENEURSHIP BY CATWOE MODEL IN GUNUNG KIDUL, CENTRAL JAVA - Deti, Regina; Evienia P, Benedicta; Kusuma, Stephanus Eri; Handayani, Penny; Amanda, Astri (Jurnal Mebis, 2023)
Increasing the economy in Gunung Kidul can be encouraged by utilizing the potential resources in the area. However, with the limitations of the community managing these resources, the economy in Gunung Kidul is still not optimal. It makes the district with the second highest poverty rate in the Province of DIY. The economic problems faced by the people of Gunung Kidul can be overcome by using a social approach. This can be developed and used as an opportunity for the local community to improve their welfare. Therefore, this study aims to develop sustainable social entrepreneurship (sustainable smart social entrepreneurship) that can be instilled in the Gunung Kidul area and have a positive economic impact on the local community. This research method uses three stages, namely problem formulation, data collection, and data analysis. Data collection was taken from literature studies, distributing questionnaires, and Focus Group Discussions (FGD) in the Gunung Kidul area. Furthermore, the data that has been collected will be mapped using CATWOE, so that we can see the causal relationships that occur. It is hoped that it can show the influence of the variables that have an impact on social entrepreneurship that is sustainable and can be invested in the Gunung Kidul area as optimally as possible.